2011
DOI: 10.2139/ssrn.1996472
|View full text |Cite
|
Sign up to set email alerts
|

The Miracle Drug: Hormone Replacement Therapy and Labor Market Behavior of Middle-Aged Women

Abstract: In an aging society, determining which factors contribute to the employment of older individuals is increasingly important. This paper sheds light on the impact of medical innovation in the form of Hormone Replacement Therapy (HRT) on employment of middle-aged women. HRT are drugs taken by middle-aged women to soften symptoms related to menopause. Before 2002, HRT products were among the most popular prescription drugs in America. We use the timing of the release of information of the potential hazardous effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We also refer to a survey by the Social Issues Research Centre (2002) because, unusually, it reports positive experiences of menopause at work. Further, we use Daysal and Orsini's (2014) IZA discussion paper because, other than two very recent papers which are outside of our date parameters (Bryson et al., 2022; Evandrou et al., 2021), this is the only academic research we have found that discusses women leaving work because of menopause. It is, in addition, methodologically robust.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also refer to a survey by the Social Issues Research Centre (2002) because, unusually, it reports positive experiences of menopause at work. Further, we use Daysal and Orsini's (2014) IZA discussion paper because, other than two very recent papers which are outside of our date parameters (Bryson et al., 2022; Evandrou et al., 2021), this is the only academic research we have found that discusses women leaving work because of menopause. It is, in addition, methodologically robust.…”
Section: Methodsmentioning
confidence: 99%
“…After the early 2000s publication of the Women's Health Initiative Study and the Million Women Study, many women stopped taking HRT because of concerns about long-term effects. In a large representative US study, Daysal and Orsini (2014) estimate a 37% decrease in its use. But for some women this backfired.…”
Section: Moulding the Body In Maw Literaturementioning
confidence: 99%
“…Some respondents did not change their working hours or their employment but worked harder in order to compensate or distract themselves from the experienced psychological symptoms [18]. Daysal and Orsini (2014) evidenced that women in the Medical Expenditure Panel Survey who had stopped taking Hormone Replacement Therapy (HRT) were more likely to leave their jobs than those who continued with the treatment. These women's symptoms interfered with their ability to work to such an extent that they felt they had to quit their jobs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Daysal and Orsini (2014) evidenced that women in the Medical Expenditure Panel Survey who had stopped taking Hormone Replacement Therapy (HRT) were more likely to leave their jobs than those who continued with the treatment. These women's symptoms interfered with their ability to work to such an extent that they felt they had to quit their jobs [19]. Paul's (2003) research reported that women lost their jobs following sickness absence or time off for treatments for menopausal transition symptoms [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study of women 40 to 55 years old who stopped taking HRT, investigators reported that women were 30% more likely to quit their jobs because of menopausal symptoms and difficulty dealing with job-related duties. 38 Studies have also reported absenteeism related to menopause symptoms. 39 Menopausal women experience harassment and discrimination by colleagues who are unsympathetic of their symptoms.…”
mentioning
confidence: 99%